EVOLUTION IN WAQF JURISPRUDENCE AND ISLAMIC FINANCIAL INNOVATION - Abdullah, Mohammad (Bank Indonesia, 2018)
This paper aims to analyse the evolutionary process in the jurisprudential structure of modern waqf (Islamic endowment) and underlines the scope of Islamic financial innovation through the mechanism of waqf. The paper proposes the innovative models of parallel waqf, waqf-based social and financial instruments, waqf-based ṣukūk, micro-takāful, and waqf-based commodity bank. The research adopts the qualitative approach and employs socio-legal research methodology for the analysis. The paper relies on desk-based research. Compared to the classical structure of waqf which was confined within the domain of a perpetual charitable institution, this paper finds that modern waqf has ushered in several new dimensions into its fold. Modern waqf is in the process of re-evolution. Waqf, in the current scenario, has evolved into a financial product, a property-conveyance tool, an instrument of contract, an investment tool, a risk mitigation mechanism and an incorporated entity. The scope of this paper is limited to analysing the jurisprudential evolution of waqf and its impact on the Islamic finance industry. It does not seek to discuss the overall role or impact of waqf on the society as a whole. This paper also does not endeavor to compare and contrast the mechanism and modalities of other philanthropic institutions vis-ā-vis waqf. This paper examines the jurisprudential underpinnings of waqf and their implications and applicability to the Islamic finance industry. The paper draws on the process of how the mechanism of waqf has already been employed to develop various innovative Islamic financial products and how this process can be a catalyst for further innovation in the Islamic finance industry. The main contribution of the paper is encapsulated in the analysis of how the jurisprudential structure of the modern waqf has been evolving in the last few decades to accommodate the modern needs of Islamic finance. It further enumerates a few innovative Islamic financial products which can be developed by exploiting the available flexibility in the evolved version of modern waqf.